PENGEMBANGAN LKPD BERBASIS KONTEKS PRIBADI PADA MATERI PELUANG KELAS VIII - Wisnu Siwi Satiti; Siti Nur Lailiyah (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2022)
There are many students that have difficulties in learning mathematics. One of them is dueto lack of meaningful learning in mathematics-classroom, so that students' learning motivation is low. Learning becomes meaningful if the concepts are presented as contexts or situations in which students